Pentatonic sequences and monaural beats to facilitate relaxation: an EEG study - Costa, Marco; Visentin, Chiara; Occhionero, Miranda; Tonetti, Lorenzo; Prodi, Nicola; Natale, Vincenzo (Frontiers in Psychology, 2024)
Introduction In two studies we investigated if specific acoustic stimulations could be more effective to induce a relaxation response in comparison to silence. Acoustic stimulations included monaural beats and musical sequences based on a pentatonic scale. Methods In the first study, 47 participants evaluated monaural beats and pentatonic sequences presented through loudspeakers and varying along three frequencies (0.2, 2, 4 Hz). In the second study, 31 participants relaxed with their eyes closed for 10 min during a passive listening of monaural beats and a pentatonic sequence presented through loudspeakers. A silence condition was introduced as control. All auditory stimuli were designed with a temporal modulation of 0.2 Hz. Concomitant EEG was recorded with a 64-channel system and spectral analysis was performed on delta, theta, alpha, beta, and gamma oscillations to test if each of the three auditory stimulations had a significant effect on EEG spectral power in comparison to silence. Results In the first study, pentatonic sequences were evaluated as more pleasant and more relaxing than monaural beats. Pleasantness and relaxation were inversely related to frequency. Visual imagery and emotion induction had higher frequency and were rated with a more positive valence in pentatonic sequences than in monaural beats. In the second study monaural beats in comparison to silence strongly decreased beta and gamma oscillations in the first three minutes and strongly increased theta oscillations in the last three minutes. Pentatonic sequences increased delta, theta, and alpha oscillations in the last three minutes while decreasing beta, and gamma oscillations for the whole auditory stimulation. Discussion The results show that auditory signals with a very low temporal modulation (0.2 Hz) could be more effective than silence in inducing a relaxation response. Although 0.2 Hz monaural beats were effective in inducing a relaxation response, they tended to be perceived as unpleasant. Pentatonic sequences could be considered as a better alternative to promote relaxation by auditory stimulation.